Average density of states of amorphous Hamiltonians: role of phonon mediated coupling of nano-clusters. (21st January 2022) - Shukla, Pragya
Abstract: Based on a description of an amorphous solid as a collection of coupled nanosize molecular clusters referred as basic blocks, we analyse the statistical properties of its Hamiltonian. The information is then used to derive the ensemble averaged density of the vibrational states (non-phonon) which turns out to be a Gaussian in the bulk of the spectrum and an Airy function in the low frequency regime. A comparison with experimental data for six glasses confirms validity of our theoretical predictions.